Fans and fan cultures : tourism, consumerism and social media - Linden, Henrik; Linden, Sara (Palgrave Macmillan, 2017)
Exploring the ambiguous relationship between fandom and consumer culture, this book provides a critical overview of fans, fan cultures and fan experiences in relation to the broader experience and transformation economy. Fans and Fan Cultures discusses key theoretical concepts concerning celebrity, fandoms, subculture, consumerism and marketing through a range of examples in film, travel and tourism, football and music. With an emphasis on social media, and how various online platforms are utilised by brands, artists and fans, the authors explore how this type of communication often contributes to trivialising authentic expressions of cultural and social values and identities.- Resumé vydavatel
Keywords: fanouškovství; fanoušci; spotřebitelské chování; cestovní ruch; fandom; fans (persons); consumer behavior; tourism; elektronické knihy; monografie; electronic books; monographs